2007
DOI: 10.1055/s-2006-958156
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Provision of Developmental Care in the Neonatal Intensive Care Unit: Neonatal Nursing Perceptions

Abstract: The role of the neonatal nurse is vital for the successful implementation of developmental care and the provision of an optimal neonatal intensive care unit (NICU) environment. The goal was to identify nurses' perceived barriers to implementation or improving developmental care in their NICUs. Nursing perceptions related to barriers for implementing developmental care were assessed using a 12-point questionnaire during two New York City Neonatal Nursing regional conferences. One hundred forty-six (86%) of 170 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 11 publications
3
43
0
4
Order By: Relevance
“…This finding was similar to previous study conducted by Franck, Bernal, and Gale (), who discussed that concerns about infant safety and co‐workers’ support could affect medical decisions. Even though nurses are capable of determining the use of KC with needed knowledge, the final implementation would greatly depend on physicians’ orders, since in China only physicians have the authority for care arrangements (Hendricks‐Munoz & Prendergast, ; Zhang et al., ). In a previous study, nurses identified nurse colleagues and staff physicians as major barriers to the implementation of developmental care (Hendricks‐Munoz et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to previous study conducted by Franck, Bernal, and Gale (), who discussed that concerns about infant safety and co‐workers’ support could affect medical decisions. Even though nurses are capable of determining the use of KC with needed knowledge, the final implementation would greatly depend on physicians’ orders, since in China only physicians have the authority for care arrangements (Hendricks‐Munoz & Prendergast, ; Zhang et al., ). In a previous study, nurses identified nurse colleagues and staff physicians as major barriers to the implementation of developmental care (Hendricks‐Munoz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff are important advocates in the utilisation of neonatal care intervention. Nurses have a responsibility for the quality care and it is essential to provide adequate education and training to improve their knowledge and to develop their skills further(Flynn & Leahy-Warren, 2010;Hendricks- Munoz & Prendergast, 2007).6 | CONCLUSIONThis survey provides the general situation of KC in China. It is an uncommon practice despite its evidence-based benefits.…”
mentioning
confidence: 99%
“…The nurse is the person who works together with the doctor in the decision conducting treatment, performing direct neonatal care and offering emotional support to families. [12] During the interviews, the nurses reported the importance of teamwork and how may be a facilitator for assistance. Teamwork is the set or group of people with complementary skills committed to each other for the mission and objectives obtained by negotiation between the actors involved and a work plan in common [13].…”
Section: Breathing Pattern Improvementmentioning
confidence: 99%
“…Sin embargo, en Introduction psychological dimensions of the family (1) . Nurses assume an important role in the context of the NICU, because they develop collaborative work with the physician in the strategies and decisions, provide direct care to the newborn and give support to the family (2) . However, there are many difficulties that nurses face regarding…”
Section: Cuidar Del Recién Nacido En La Presencia De Sus Padres: Vivementioning
confidence: 99%